1994
DOI: 10.3109/17453679408995458
|View full text |Cite
|
Sign up to set email alerts
|

Decreased broadband ultrasound attenuation of the calcaneus in women with fragility fracture: 85 Colles' and hip fracture cases versus 77 normal women

Abstract: The broadband ultrasound attenuation (BUA) of the right calcaneus was measured in 49 women with Colles' fracture, in 36 women with hip fracture, and in 77 normal women. All were postmenopausal, and the fractures were all of fragility type. BUA correlated with age only in the normals. BUA distinguished between the fracture cases with sensitivities of 97 percent and 70 percent and specificities of 72 percent and 92 percent at 61 dB/MHz and 51 dB/MHz, respectively. The women with hip fracture had lower BUA than t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

1995
1995
1999
1999

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 16 publications
0
7
0
1
Order By: Relevance
“…Several cross-sectional and prospective studies have demonstrated that subjects with fractures have lower speed of sound values and BUA than subjects without fractures [5][6][7][8]22]. The age-adjusted odds ratio for lowtrauma fracture for each 1 SD decrease in either speed of sound or BUA in peripheral measurement sites ranges from 1.24 at the patella [23] to 3.7 at the calcaneus [24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several cross-sectional and prospective studies have demonstrated that subjects with fractures have lower speed of sound values and BUA than subjects without fractures [5][6][7][8]22]. The age-adjusted odds ratio for lowtrauma fracture for each 1 SD decrease in either speed of sound or BUA in peripheral measurement sites ranges from 1.24 at the patella [23] to 3.7 at the calcaneus [24].…”
Section: Discussionmentioning
confidence: 99%
“…One of the most important questions concerning the use in a clinical setting of quantitative ultrasound (QUS) is whether this technology is capable of detecting subjects at risk of fracture. Cross-sectional studies have demonstrated that subjects with osteoporotic fractures have lower values of ultrasound velocity and of broadband ultrasound attenuation (BUA) than subjects without fractures [7,8]. In the majority of studies the calcaneus was used as the measurement site [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Although the majority of investigations have been made with QUS at the calcaneus, finding associations with vertebral [43, 56,57,[61][62][63][64], hip and forearm fractures [65,66], recently reports have begun to appear showing similar capabilities for ultrasound measurements at the patella, tibia and phalanges [46,62,[67][68][69][70][71][72]. Indeed, tibial SOS has been associated with incident non-spine fractures [62].…”
Section: Conclusion Drawn From Current In Vivo Studies?mentioning
confidence: 99%
“…Many clinical studies have shown a reduction in QUS values in women with primary osteoporosis, even when osteoporosis was defined by different methods: densitometric, radiographic (detection of vertebral fractures), history of recent hip fracture, and self-reported history of previous osteoporotic fractures (5,12,(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29). In preliminary studies, QUS has also been shown to be useful in patients with secondary osteoporosis, including patients with inflammatory bowel disease (30), chronic renal failure (31), reflex sympathetic dystrophy (32), bronchial asthma receiving chronic steroid therapy (33), spaceflight-induced bone loss (34), young ballet dancers (35), glucocorticoid-induced osteoporosis (36), and rheumatoid arthritis (37), and in normal pregnancy (38).…”
Section: Tanveer E Towheedmentioning
confidence: 99%